2013
DOI: 10.1136/bmjopen-2013-003946
|View full text |Cite
|
Sign up to set email alerts
|

Parent-led or baby-led? Associations between complementary feeding practices and health-related behaviours in a survey of New Zealand families

Abstract: ObjectiveTo determine feeding practices and selected health-related behaviours in New Zealand families following a ‘baby-led’ or more traditional ‘parent-led’ method for introducing complementary foods.Design, setting and participants199 mothers completed an online survey about introducing complementary foods to their infant. Participants were classified into one of four groups: ‘adherent baby-led weaning (BLW)’, the infant mostly or entirely fed themselves at 6–7 months; ‘self-identified BLW’, mothers reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
114
1
14

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(135 citation statements)
references
References 30 publications
6
114
1
14
Order By: Relevance
“…The findings support previous smaller studies (5,(8)(9)(10) suggesting BLW may not increase choking risk. The findings support previous smaller studies (5,(8)(9)(10) suggesting BLW may not increase choking risk.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The findings support previous smaller studies (5,(8)(9)(10) suggesting BLW may not increase choking risk. The findings support previous smaller studies (5,(8)(9)(10) suggesting BLW may not increase choking risk.…”
Section: Discussionsupporting
confidence: 90%
“…In two studies in New Zealand, although approximately onethird of babies in both studies (8,9) experienced at least one choking episode, there was no difference in occurrence between infants following a baby-led or standard weaning approach (9) . In two studies in New Zealand, although approximately onethird of babies in both studies (8,9) experienced at least one choking episode, there was no difference in occurrence between infants following a baby-led or standard weaning approach (9) .…”
Section: Introductionmentioning
confidence: 90%
“…A randomized, controlled selection method is important because parents who follow BLW have been shown to differ from parents following the traditional methods of complementary feeding in demographic, psychological and parenting characteristics known to also be associated with bodyweight . Two cross‐sectional studies have investigated rates of obesity in infants following BLW .…”
Section: Discussionmentioning
confidence: 99%
“…Data has to rely on self-identification of choking (as against gagging) and self-report. One study examining rates in New Zealand found no difference in choking incidences between groups [16], which was supported in the larger-scale BLISS trial work [25]. However, the BLISS data noted that choking occurred at least once in all weaning groups at a rate of 35% of infants.…”
Section: Is the Approach Safe?mentioning
confidence: 95%